PRODUKSI IKLAN LAYANAN MASYARAKAT TEMAN BUS DENGAN GAYA CERITA SINEMATIK DI PT HAI BANANA PRODUCTION - Kristi, Ni Kadek Ayu Widia; Puriartha, I Kadek; Yasa, Desak Putu Yogi Antari Tirta (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2025)
Traffic in Bali is increasing with the growth of private vehicles and tourists. The government presents Teman Bus Bali as a publik transportation solution based on the Buy the Service (BTS) program. This research aims to create a Publik Service Announcement (PSA) with a sinematik story style that is effective in attracting publik attention to use Teman Bus. The methods used include data collection, surveis, and observations to understand publik behavior towards publik transportation. The results of the report show that the sinematik story style successfully conveys messages through immersive visuals and narratives, increasing the appeal of Teman Bus as an alternative transportation. With creative visuals and a persuasive approach, this PSA is expected to reduce the use of private vehicles, overcome congestion, and support community mobility. This project is an important reference for the production of PSAs in the transportation sector to encourage changes in publik behavior towards the use of publik transportation.